Write x^n = e^lnx^n = e^nlnx and use the fact proved in class that if f(x) =
e^g(x) then f'(x) = e^g(x)g'(x) to show that in general the derivative of
x^n is nx^(n-1)
Please help me to prove it
Have a nice day!
Write x^n = e^lnx^n = e^nlnx and use the fact proved in class that if f(x) =
e^g(x) then f'(x) = e^g(x)g'(x) to show that in general the derivative of
x^n is nx^(n-1)
Please help me to prove it
Have a nice day!
Please help you to prove it? Most of the work has already been done for you. You have a VERY simple formula to follow: $\displaystyle \displaystyle \begin{align*} f'(x) = e^{g(x)}\,g'(x) \end{align*}$. Apply it!